Kebijakan Pelayanan Parkir Tepi Jalan Umum Dalam Peningkatan Pendapatan Asli Daerah Kota Gorontalo - Hasan, Sri Rahayu M. (Program Studi Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Tadulako, 2026)
Parking is a crucial component of the transportation system as it is the starting and ending point of every vehicle journey. This means that parking facilities are crucial for the overall efficiency of the transportation system. The purpose of this study is to examine the following stages in the implementation process of the Public Service Digitalization Policy in Limba U1 Village, South Kota District, Gorontalo City: 1) Agenda Preparation, 2) Policy Formulation, 3) Policy Adoption, 4) Policy Implementation, and 5) Policy Evaluation. This study focuses on the aforementioned. The method used in this study is qualitative. The results show that the public roadside parking service policy in Gorontalo City experiences weaknesses in all stages of the process: the agenda preparation is not based on empirical data and stakeholder participation, so that problems have not been systematically mapped; the policy formulation is still conventional, has not adopted digital technology, and does not involve field implementers; the adoption stage emphasizes formal legal aspects without considering resource readiness and adequate socialization; during implementation there are levy leaks, weak supervision, and low compliance resulting in revenue not reaching the target; Meanwhile, evaluations are purely administrative, unsystematic, and lack clear feedback mechanisms. As a result, policies have not been implemented effectively, their contribution to Regional Original Income has not been optimal, and the quality of service perceived by the public remains unsatisfactory.